Phase IV Postmarketing Surveillance Study Shows Continued Efficacy and Safety of Stempeucel in Patients with Critical Limb Ischemia Due to Buerger's Disease. (13th September 2021) - Gupta, Pawan Kumar; Dutta, Santanu; Kala, Sanjay; Nekkanti, Muralikrishna; Desai, Sanjay C.; Mahapatra, Subhendu S.; Dhar, Anita; Raju, Radhakrishnan; M., Rajkumar; Behera, Arunanshu; P., Shivashankar; Raviraja, N.S.; et al.
Abstract: Buerger's disease or thromboangiitis obliterans is a type of obstructive vascular diseases categorized as vasculitis and usually present in 95% of young smoker men. The main pathogenetic mechanism is interplay between immune system and inflammation. Earlier our phase II study has shown that Stempeucel is safe when injected at 2 million cells/kg body weight by virtue of its anti-inflammatory, immunomodulatory, and angiogenetic properties. The present study was conducted to further assess the safety and efficacy of Stempeucel in critical limb ischemia due to Buerger's disease after obtaining approval from Indian FDA based on the data generated in the phase II study. This is an open label, multicenteric phase IV PMS study conducted across India with experienced vascular surgeons. Fifty patients of critical limb ischemia due to Buerger's disease with Rutherford III-5 or III-6 were included in the study and each individual received a dose of 2 million cells/kg body weight of Stempeucel in the calf muscles and around the ulcer. These patients were evaluated over 12 months from drug administration. The present study showed the continued long term efficacy over a period of 12 months follow up in these patients corroborating the result obtained in the previous phase II studies. There was significant improvement in rest pain, ankle systolic pressure, and ankle brachial pressure index with accelerated ulcer healing. In conclusion, the present study shows that the intramuscular administration of Stempeucel continues to be safe, tolerable, and effective alternative treatment in patients with Buerger's disease. : Stempeucel showed the continued long term efficacy over a period of 12 months follow up in patients with CLI due to Buerger's disease. Significant improvement in rest pain, ankle systolic pressure and ankle brachial pressure index with accelerated ulcer healing was observed. Stempeucel continues to be safe, tolerable and effective alternative treatment in patients with Buerger's disease.